ASSOCIATION BETWEEN BEHAVIOURAL FACTORS AND OVERWEIGHT/OBESITY AMONG PEOPLE LIVING WITH HIV AT KAJJANSI HEALTH CENTRE IV. A CROSS SECTIONAL STUDY. - Kibuuka, Frank; Kungu, Joseph; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2024)
Background Overweight and obesity are major public health concerns globally, contributing to a significant burden of chronic diseases such as cardiovascular disease, diabetes, and certain cancers. These conditions are multifactorial, with a growing body of evidence highlighting the role of behavioral factors in their development and progression. This study aimed to determine the association between behavioral factors and overweight/obesity among PLWH at Kajjansi Health Centre IV. Methodology A descriptive cross-sectional study with a mixed-methods approach was conducted on 50 PLWH. Data were collected through questionnaires, interviews, and medical record reviews. Descriptive statistics, chi-square tests, t-tests, and multiple logistic regression analyses were performed to examine associations between various factors and overweight/obesity status. Results At baseline, 80.0% (n = 40) of participants were classified as overweight or obese. Among those with low dietary diversity, 100.0% (n = 4) were overweight or obese, compared to 71.0% (n = 22) of those with moderate dietary diversity and 93.3% (n = 14) of those with high dietary diversity. However, this association was not statistically significant (χ² = 4.247, df = 2, p = 0.120). Conclusion The findings conclude no significant association between dietary diversity and obesity status, a significant association between physical activity and obesity status only at the end line, and no significant relationship between sedentary behavior and obesity. Recommendation There should be practical interventions that include tailored nutritional counseling and physical activity programs that consider unique sociocultural contexts.